Peritoneal Dialysis Catheters, Insertion Methods and Complications - Paudel, Klara (Pakistan Journal of Kidney Diseases, 2021)
The success of peritoneal dialysis (PD) and the PD program lies in a well-functioning catheter without infections. There are various types of catheters available and various insertion methods, although the difference in function and the outcome results are not markedly differentiated. In this review the types of commonly used peritoneal catheters and the variety of insertion methods will be introduced, along with special techniques and special catheters. This article will also list the complications that arise early, within 30 days of insertion. Comparing the main standard catheter variations and insertion methods, there is no difference in function and complications.